Care Perception of Postnatal Mother on Care during Labour in Tertiary Level Hospital, Nepal - Gautam Bhattarai, Saraswoti Kumari; Dhakal, Kamala; Pandey, Apsara; Gautam, Kanchan (Journal of Advanced Academic Research, 2021)
Background: Labour and delivery experience is one of the most significant events in a woman’s life. Support in labour has an impact on the childbirth experience and childbirth outcomes. A positive childbirth experience can help in mastering the major change in life. Therefore, the objective of this study was to find out postnatal mothers' perception on care during labour.Methods: A descriptive cross-sectional design was used to explore the perception on care during labour of postnatal mothers in postnatal ward Tribhuvan University Teaching Hospital. Total 294 postnatal mothers with normal delivery were selected by purposive sampling method after receiving ethical approval from research department of Institute of Medicine and concerned authority. Data was analyzed by using descriptive as well as inferential statistics.Results:  Among 294 women; 208(70.75%) were received care on infection prevention, 160(54.42%) received bladder care, 175(59.66%) received care on hydration maintenance, 149(50.57%) received care on injury prevention, 103(34.88%) care on comfort measures, 180(61.14%) care on information, 207(70.54%) care on emotional support, and 201(68.31%) care immediately after childbirth. There is significant relationship among different types of care during labour (such as emotional support (44.44%), infection prevention care (19.7%), care for bladder empty (14.5%), maintenance of hydration (17.1%), care for prevention of injury (31.9%), care on pain relieve and comfort measures (50.1%), informational care (64.5%), and care immediately after delivery (18.5%)) and overall perception on care during labour.  The perception level was based on mean score and was categorized as; below 3 is negative perception, 3 and above is positive perception. The finding of this study shows that 93(31.6%) postnatal mothers were perceived care negatively and 201(68.4%) perceived care positively during labour. It indicates that care during labour needs to be improved for best care perception.Conclusions: Women expect professional, supportive and respectful care during labour. Continuous care and support during labour has meaningful benefits for women and infants. It indicates that the care during labour need to be improved for best care perception.